Optimization of a peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) method for the detection of bacteria and disclosure of a formamide effect - Rita S. Santos (2014)
Despite the fact that fluorescence in situ hybridization (FISH) is a well-established technique to identify microorganisms, there is a lack of understanding concerning the interaction of the different factors affecting the obtained fluorescence. In here, we used flow cytometry to study the influence of three essential factors in hybridization - temperature, time and formamide concentration - in an effort to optimize the performance of a Peptide Nucleic Acid (PNA) probe targeting bacteria (EUB338). The PNA-FISH optimization was performed with bacteria representing different families employing response surface methodology. Surprisingly, the optimum concentration of formamide varied according to the bacterium tested. While hybridization on the bacteria possessing the thickest peptidoglycan was more successful at nearly 50% (v/v) formamide, hybridization on all other microorganisms appeared to improve with much lower formamide concentrations. Gram staining and transmission electron microscopy allowed us to confirm that the overall effect of formamide concentration on the fluorescence intensity is a balance between a harmful effect on the bacterial cell envelope, affecting cellular integrity, and the beneficial denaturant effect in the hybridization process. We also conclude that microorganisms belonging to different families will require different hybridization parameters for the same FISH probe, meaning that an optimum universal PNA-FISH procedure is non-existent for these situations.